Fabrication and investigation on microsphere laser based on Er-doped silica glass : M.A. Thesis. Nano Materials and Devices - Hoang, Quang Hung (Đại học Quốc gia Hà Nội, 2017)
Chapter 1: Microsphere Cavity. Chapter 2: Tapered optical fiber coupling. Chapter 3: Microsphere laser based on Er-doped silica glass